2007
DOI: 10.1128/jb.01860-06
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Transposon Insertion Mutations inBacillus anthracis: Global Identification of Genes Required for Sporulation and Germination

Abstract: A transposon site hybridization (TraSH) assay was developed for functional analysis of the Bacillus anthracis genome using a mini-Tn10 transposon which permitted analysis of 82% of this pathogen's genes. The system, used to identify genes required for generation of infectious anthrax spores, spore germination, and optimal growth on rich medium, was predictive of the contributions of two conserved hypothetical genes for the phenotypes examined.The goal of obtaining a detailed understanding of Bacillus anthracis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The amplicon was then digested with KpnI and ligated into the plasmid pASD2, an E. coli-B. cereus shuttle vector with a thermosensitive origin of replication in B. cereus (14). The resulting plasmid, pMFB4 (pASD2::exsM 200bp ), was passaged through E. coli INV110 (dam dcm mutant) to obtain unmethylated DNA and then introduced into B. cereus ATCC 4342 by electroporation, following a previously described protocol (62).…”
Section: Creation Of B Cereus and B Anthracis Mutantsmentioning
confidence: 99%
“…The amplicon was then digested with KpnI and ligated into the plasmid pASD2, an E. coli-B. cereus shuttle vector with a thermosensitive origin of replication in B. cereus (14). The resulting plasmid, pMFB4 (pASD2::exsM 200bp ), was passaged through E. coli INV110 (dam dcm mutant) to obtain unmethylated DNA and then introduced into B. cereus ATCC 4342 by electroporation, following a previously described protocol (62).…”
Section: Creation Of B Cereus and B Anthracis Mutantsmentioning
confidence: 99%
“…Spore germination has been studied intensively. Recently, 31 genes required for B. anthracis sporulation and germination were identified [34]. A few studies have been reported on how the expression of sporulation and germination related genes in B. anthracis spores are affected under different physical intervention techniques, such as heat treatment, pasteurization, and microfiltration [35].…”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the effect of SWCNTs-NIR treatment on B. anthracis spores at the molecular level, real-time PCR was used to test the expression levels of six germination-related genes identified by the transposon site hybridization (TraSH) assay [34], seven virulence-related genes and three regulatory genes. Table  1 shows the fold changes in the expression levels of all the detected genes in B. anthracis spores upon SWCNTs-NIR treatment in comparison to the untreated spores.…”
Section: Resultsmentioning
confidence: 99%
“…These transposons, both Mariner and mini -Tn 10 -based systems, do not appear to preferentially insert into the virulence plasmids, and transposon insertions have been isolated in a wide variety of chromosomal locations (see the references cited in Table 4.1 ). Indeed, the mini -Tn 10 system described by Day et al (2007) associated with greater than 80% of the genes in the B. anthracis strain tested. This improved chromosome coverage allowed for TraSH analysis of genes important in growth, sporulation, and germination in laboratory growth media.…”
Section: Transposonsmentioning
confidence: 99%
“…This improved chromosome coverage allowed for TraSH analysis of genes important in growth, sporulation, and germination in laboratory growth media. All of these studies were performed with non -pathogenic strains of B. anthracis , but Cote et al (2008) used the miniTn 10 system of Day et al (2007) to identify a protein recognized by anti -spore antibodies from a fully virulent strain.…”
Section: Transposonsmentioning
confidence: 99%